Transfer of property based on property law rules and contract law rules under forthcoming Kosovo draft-civil code - Gashi, Haxhi (Array, 2021)
In most civil law jurisdictions, the contract is the most used derivative title for the transfer of ownership (movable and immovable property). Very often, the law of property and law of contract are seen as distinct and one can envisage their role from different legal perspectives. This is closely connected with the type of transfer system based on whether the (Austrian) causal system, (German) abstract system or (French) consensual system is applicable. Kosovo is in the process of civil law codification and the Kosovo Draft-Civil Code which has followed the application of the causal system of transfer of property and such an above mentioned interaction of these two branches of civil law is mandatory, and only with a common survey can the contractual transfer of property be illustrated. The aim of this paper is to focus solely on the influence of contract law rules in connection with the acquisition of ownership over movable and immovable property determined by Kosovo Draft-Civil Code.